MILITARY PEDAGOGY: DIDACTICS OF MILITARY-PEDAGOGICAL RESEARCH AND PROBLEMS OF EDUCATION OF MILITARY SERVANTS (Academicia Globe: Inderscience Research, 2021)
This article discusses the development of military pedagogy as a necessary tool for the comprehensive training of officers, military pedagogical research and modern problems of didactics and training of military personnel. Methodological bases of national military pedagogy and application in the current conditions of development of military education, the level of competence of officers in working with personnel, features of formation of military professional powers are reflected.